Ammonia clathrate hydrates as new solid phases for Titan, Enceladus, and other planetary systems - Shin, Kyuchul; Kumar, Rajnish; Udachin, Konstantin A.; Alavi, Saman; Ripmeester, John A. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
There is interest in the role of ammonia on Saturn's moons Titan and Enceladus as the presence of water, methane, and ammonia under temperature and pressure conditions of the surface and interior make these moons rich environments for the study of phases formed by these materials. Ammonia is known to form solid hemi-, mono-, and dihydrate crystal phases under conditions consistent with the surface of Titan and Enceladus, but has also been assigned a role as water-ice antifreeze and methane hydrate inhibitor which is thought to contribute to the outgassing of methane clathrate hydrates into these moons' atmospheres. Here we show, through direct synthesis from solution and vapor deposition experiments under conditions consistent with extraterrestrial planetary atmospheres, that ammonia forms clathrate hydrates and participates synergistically in clathrate hydrate formation in the presence of methane gas at low temperatures. The binary structure II tetrahydrofuran + ammonia, structure I ammonia, and binary structure I ammonia + methane clathrate hydrate phases synthesized have been characterized by X-ray diffraction, molecular dynamics simulation, and Raman spectroscopy methods.
Keywords: ethane; hydrate inhibitors; hydrogen bonding; ice; single crystal X-ray diffraction